EDUKASI TEKNIK FINGER HOLD DALAM PENGELOLAAN NYERI DISMENORE REMAJA PUTRI - Erindia, Firnanda; Revani, Hilda Dea; Budiawan, Putri Ayu Madedi (Community Development in Health Journal, 2025)
Introduction & Aim: Dysmenorrhea is a reproductive health problem commonly experienced by adolescent girls and may affect daily activities, learning concentration, and overall quality of life. This community service activity aimed to improve adolescent girls’ knowledge about dysmenorrhea and introduce the finger hold technique as one of the non-pharmacological methods to reduce pain. Method of Activity: The activities included lectures, interactive discussions, and demonstrations of the finger hold technique using media such as booklets, videos, and presentations. Evaluation was conducted through pre-test and post-test involving 12 adolescent girls aged 15–19 years with a history of dysmenorrhea. Results: The results showed that before the education was provided, most respondents had poor knowledge (67%). After the intervention, there was a significant improvement, with good knowledge increasing to 50%, fair knowledge to 33%, and poor knowledge decreasing to 17%. Discussion: Education combined with the demonstration of the finger hold technique was effective in improving adolescent girls’ knowledge about dysmenorrhea and its management. It is recommended that adolescent girls apply the finger hold technique in their daily lives, schools actively participate in providing reproductive health education, and healthcare workers expand counseling using interactive methods.